Estruturas urbanas comparadas: Estados Unidos e Brasil - Ruiz, Ricardo Machado (Estudos Econômicos (São Paulo), 2005)
The literature on urban economics usually point out the developing countries as those ones with urban structure extremely concentrated and unequal, and the developed countries as those countries with a better distribution of cities. This paper compares the national urban structures of two countries: the USA, a developed country, and Brazil, a developing country.